Why conclusions from platinum model surfaces do not necessarily lead to enhanced nanoparticle catalysts for the oxygen reduction reaction. Issue 3 (19th December 2016) - Calle-Vallejo, Federico; Pohl, Marcus D.; Reinisch, David; Loffreda, David; Sautet, Philippe; Bandarenka, Aliaksandr S.
Abstract : Platinum model-surface and nanoparticle catalysts for the oxygen reduction reaction are enhanced by the presence of concave sites. Abstract : Experiments on model surfaces commonly help in identifying the structural sensitivity of catalytic reactions. Nevertheless, their conclusions do not frequently lead to devising superior "real-world" catalysts. For instance, this is true for single-crystal platinum electrodes and the oxygen reduction reaction (ORR), an important reaction for sustainable energy conversion. Pt(111) is substantially enhanced by steps, reaching a maximum at short terrace lengths of 3–4 atoms. Conversely, regular platinum nanoparticles with similar undercoordinated defects are less active than Pt(111) and their activity increases alongside the terrace-to-defect ratio. We show here that a model to design ORR active sites on extended surfaces can also be used to solve this apparent contradiction and provide accurate design rules for nanoparticles. Essentially, only surfaces and nanostructures with concave defects can surpass the activity of Pt(111), whereas convex defects are inactive. Importantly, only the latter are present in regular nanoparticles, which is why we design various concave nanoparticles with high activities.